Permintaan Daging Sapi di Kota Banjarmasin - Munawarah; Fahrety, Eny (PPJP ULM, 2019)
This study aims to discover how the beef price, the broiler price, the price of gabus fish, the cost of salty telang fish, and per capita income influence demand for beef at Banjarmasin city and what the factor is the most dominant effect of beef at Banjarmasin city. The study used data for six years from 2010 until 2015 years in a matter of months. This study used analyze technic regression linear double with variable dependent demand of beef(Y) and independent variable price of beef(X1) price of broiler (X2), cost of gabus fish (X3), price of salty telang fish (X4) and per capita income (X5). From this study result, variable fee salted telang fish are influential in the demand of beef at Banjarmasin city and variable beef price, broiler price, gabus fish price and per capita income with all not influential significate to face the need of meat at Banjarmasin City. The factor the most dominant demand of beef is variable the salty telang fish.